The impact of universal mental health screening on stigma in primary schools - Annabel Songco; Deanna A. Francis; Emma A. McDermott; Chloe Y. S. Lim; Abigail Allsop; Joseph Croguennec; Gemma Sicouri; Andrew Mackinnon; Jennifer L. Hudson (Child and Adolescent Psychiatry and Mental Health)
Abstract Background Primary school students struggling with mental health are less likely than high school students to access mental health care, due to barriers such as mental health stigma and low mental health literacy among children and parents. The near universal reach of schools offers a potential avenue to increase access to mental health care through early identification. The potential risks of this approach also need to be understood. This study monitored the impact of universal screening for mental health symptoms on stigma and mental health outcomes for primary school students. Methods Across 6 primary schools, a cluster randomised controlled trial allocated schools to one of two conditions. Conditions varied based on the order and frequency of symptom and stigma questionnaires. A sample of 798 children (8 to 13 years; Mage = 10.29) completed assessments at baseline, 6-week, and 12-week follow-ups. Results Significant time-by-group interaction effects were present, indicating differing changes in mental health stigma between groups. Follow-up analyses of subscales showed significant time-by-group interaction effects for concerns around self-stigma and secrecy, but not for public stigma. The frequency and presentation order of the questionnaires impacted on mental health stigma. Initially, children reporting on mental health symptoms before stigma, reported heightened stigma, but over time, those receiving more frequent presentations of the symptom check experienced an overall stigma reduction, contrasting with an increase in the comparison group. Conclusion The frequency and presentation order of mental health symptom assessments impact children’s reports of mental health stigma, underscoring the importance of screening context. Potential screening harms, such as exacerbating self-stigma and secrecy, warrant consideration. Addressing stigma-related barriers is crucial for enhancing mental health care access for children in schools. Trial registration Australian and New Zealand Clinical Trials Registry (ACTRN12622001114730) https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=384472 Date of trial registration: 12th August 2022.